Honest signaling of cooperative intentions. (13th May 2020) - Roberts, Gilbert
Abstract: Trust can transform conflicting interests into cooperation. But how can individuals know when to trust others? Here, I develop the theory that reputation building may signal cooperative intent, or "trustworthiness." I model a simple representation of this theory in which individuals 1) optionally invest in a reputation by performing costly helpful behavior ("signaling"); 2) optionally use others' reputations when choosing a partner; and 3) optionally cooperate with that partner. In evolutionary simulations, high levels of reputation building, of choosing partners based on reputation, and of cooperation within partnerships emerged. Costly helping behavior evolved into an honest signal of trustworthiness when it was adaptive for cooperators, relative to defectors, to invest in the long-term benefits of a reputation for helping. I show using game theory that this occurs when cooperators gain larger marginal benefits from investing in signaling than do defectors. This happens without the usual costly signaling assumption that individuals are of two "types, " which differ in quality. Signaling of trustworthiness may help explain phenomena such as philanthropy, pro-sociality, collective action, punishment, and advertising in humans and may be particularly applicable to courtship in other animals. Abstract : Cooperative reputations can honestly signal trustworthiness when it pays for co-operators but not defectors to invest for the long term. Here I use evolutionary simulation and game theory to show how the basic difference in strategy between co-operators and defectors can allow an honest signaling system to emerge. Those choosing partners can then use generous reputations as honest signals of future behavior. This may help explain the formation of social and sexual partnerships.